Implementation of Financial Reports in Accordance with EMKM SAK in an Effort to Improve the Performance of Mejiku Florist UMKM in Makassar - Nurul Izmi Muhajir; Rasika Salsabila; Wahyuni; Muchriana Muchran (www.amertainstitute.com, 2025)
This research aims to explore the implementation of financial statements in accordance with SAK EMKM in an effort to improve the performance of Mejiku Florist Micro, Small, and Medium Enterprises (MSMEs) in Makassar. Using qualitative approaches and case study methods, this study collected data through participatory observation, in-depth interviews, and documentation. The results of the study show that although the owner of Mejiku Florist is aware of the importance of financial statements, the recording practices carried out are still simple and not fully in accordance with applicable accounting standards. Obstacles faced include a low understanding of accounting, lack of formal training, and limited human resources. These findings indicate that to improve the performance of MSMEs, a better understanding of financial statements and greater support from related parties is needed. This research provides important insights for stakeholders in formulating more effective strategies to support the development of MSMEs in Indonesia.